Strategi Pengembangan UMKM Melalui Legalitas Usaha Dan Sosial Media Di Banjarbendo Sidoarjo - Faizatul Isnaini; Briliantine Caesar Eka Wantoro; Laily Muzdalifah (UNIB Press, 2023)
Micro, small and medium enterprises (MSMEs) as a factor of economic growth are strategically positioned to accelerate structural changes to improve the standard of living of society in general. MSME's role is to expand the supply of employment and become a resource for sustainable economic growth and equity in increasing income. The research object for the Banana Nuna Banana Chips industry is located in Banjarbendo Village, Sidoarjo District, Sidoarjo Regency. The method used is in the form of marketing assistance using social media in the form of Instagram and whatsapp business. Primary data sources were obtained in the form of interviews, observation and documentation, as well as secondary data from books and journals were also used to support this assistance. Based on the research results, information was obtained that the factors inhibiting the development of the banana nuna banana chip industry were media for promotion, marketing and capital. With this assistance, the MSME development strategy will be known. The business development strategy includes external factors, namely economic, social and environmental. Apart from that, strategy includes internal factors such as management, marketing, finance, and product.